Etyka w społecznej gospodarce rynkowej - Przybyciński, Tomasz (Annales. Etyka w Życiu Gospodarczym, 2008)
Respecting the rights of man, the social market economy is aimed at maintaining a high rate of economic growth, price stability, full employment, healthy competition, good working conditions and public services. That is just why the social market economy is not far removed from the objective demands of the moral order, from the exigencies of justice and social love.